Cholesterol and triglyceride levels in first-episode psychosis: systematic review and meta-analysis. (December 2017) - Pillinger, Toby; Beck, Katherine; Stubbs, Brendon; Howes, Oliver D.
Abstract : Background: The extent of metabolic and lipid changes in first-episode psychosis (FEP) is unclear. Aims: To investigate whether individuals with FEP and no or minimal antipsychotic exposure show lipid and adipocytokine abnormalities compared with healthy controls. Method: We conducted a meta-analysis of studies examining lipid and adipocytokine parameters in individuals with FEP and no or minimal antipsychotic exposure v. a healthy control group. Studies reported fasting total cholesterol, low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, triglycerides and leptin levels. Results: Of 2070 citations retrieved, 20 case–control studies met inclusion criteria including 1167 patients and 1184 controls. Total cholesterol and LDL cholesterol levels were significantly decreased in patients v. controls, corresponding to an absolute reduction of 0.26mmol/L and 0.15mmol/L respectively. Triglyceride levels were significantly increased in the patient group, corresponding to an absolute increase of 0.08 mmol/L However, HDL cholesterol and leptin levels were not altered in patients v. controls. Conclusions: Total and LDL cholesterol levels are reduced in FEP, indicating that hypercholesterolaemia in patients with chronic disorder is secondary and potentially modifiable. In contrast, triglycerides are elevated in FEP. Hypertriglyceridaemia is a feature of type 2 diabetes mellitus, therefore this finding adds to the evidence for glucose dysregulation in this cohort. These findings support early intervention targeting nutrition, physical activity and appropriate antipsychotic prescription.